Implementing an interprofessional first-year teamwork project: some key reflections. Issue 5 (14th May 2013) - McNaughton, Susan Maree
Abstract: Implementing an interprofessional teamwork project for first-year students presents pedagogical and practical challenges. While transferable skills and attributes are important, engagement of students with limited professional experience in teamwork depends on relevance to current learning needs. This report outlines principles learned from planning and implementing a teamwork project for an interprofessional health administration and service development course. Practising interprofessional teamwork as leaders and teachers, aligning with previous, current and future teamwork content and processes and responding to student feedback and achievement have been the key factors in shaping the project over three semesters. Face-to-face and online interprofessional teamwork learning has necessitated developing resources that support self-direction, using familiar technology and providing enabling physical environments. Implications for first-year interprofessional teamwork are that structured well-resourced processes, responsiveness and alignment of learning all improve student outcomes.